IDEOLOGICAL AND ARTISTIC FEATURES OF THE “NURALI” EPICS - Feruzbek Normatov (Bright Mind Publishing, 2025)
In this article, examples of national values of the Uzbek people have an ancient history. One of the examples of this enormous treasure is the dastans, which to this day serve as a leading source in educating people in the spirit of love and devotion to the Motherland and the people. In this article, the ideological and artistic features of the “Nurali” cycle of epics are scientifically analyzed.
Keywords: Cycle, people, epic, song, child, epic memory, epic, biography